(1)(-a^2)^3*a^3+(-4a)^2*a^7-5(a^3)^3 =-a^6*a^3+16a^2*a^7-5a^9=-a^9+16a^9-5a^9=10a^9(2)(a-2b)^3*(2b-a)^4/(a-2b)^6=(a-2b)^3*(a-2b)^4/(a-2b)^6=(a-2b)^(3+4-6)=a-2
计算:(1)(-a^2)^3*a^3+(-4a)^2*a^7-5(a^3)^3 (2)(a-2b)^3*(2b-a)^4
1个回答
相关问题
-
(a^2+b^3)(2a^2+2b^3)(3a^2+3b^3)(4a^2+4b^3)(4a^2+4b^3)(5a^2+5
-
计算:(-4a^3+12a^2b-7a^3b^2)/(-4a^2)
-
设集合A={2,4,a^3-2a^2-a+7},B={1,5a-5,-1/2a^2+3/2a+4,a^3+a^2+3a+
-
计算(-a^2)3^b^3-2b*(a^3)^2*b^2-a^4*(-b^^3*(-a)^2
-
计算(-a^2)3^b^3-2b*(a^3)^2*b^2-a^4*(-b)^3*(-a)^2
-
计算:-3x+(x-1)-(3x-3)= 2(a-2)-3(a+1)= -(5a-4b)+2(a-2b)=
-
化简(1)3a2-2a-3+4a2-7a+5;(2)2(2a-3b)+3(2b-3a);(3)2a2-[[1/2](ab
-
计算:1.(2x+7)(3x-4)+(3x+5)(3-2x)2.[(a-3b)(a+3b)-(3b-a)²]÷
-
计算:[-a(b^2)]^2[(-a^4)(b^3)]^3[(-3a^2)b]
-
已知A={2,4,a^3-2a^2+7},B={-4,a+3,a^2-2a+2,a^3+a^2+3a+7},若A∪B={